Hakikat Konseling Multibudaya, Pengertian Budaya, dan Kebudayaan - Putri Inayah; Bakhrudin All habsy; Ari Khusumadewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Indonesia is a country rich in cultural and ethnic diversity. Each culture serves as a unique identity for different ethnic groups, shaping the behavior, traditions, and way of life of its people. This multicultural diversity presents challenges in counseling practice, especially for counselors who must understand and respond to the needs of clients from diverse cultural backgrounds. Multicultural counseling emerges as an approach that is sensitive to cultural differences, emphasizing the importance of understanding diverse values, norms, and cultural perspectives to ensure effective counseling processes. This article describes the essence of multicultural counseling, the concept of culture, and culture as a system of societal values and practices. Using a qualitative descriptive method with a literature study approach, this research provides an in-depth analysis of the counselor’s role in addressing cultural diversity and the implications of cultural values in guidance and counseling practice. The findings indicate that a deep understanding of the client's culture and the application of cultural relativism principles are crucial to avoid cultural bias and provide fair and empathetic services.